Energy dispersive spectroscopy‐scanning transmission electron microscope observations of free radical production in human polymorphonuclear leukocytes phagocytosing non‐opsonized Tannerella forsythia. Issue 6 (24th April 2017) - Moriguchi, Keiichi; Hasegawa, Yoshiaki; Higuchi, Naoya; Murakami, Yukitaka; Yoshimura, Fuminobu; Nakata, Kazuhiko; Honda, Masaki
Abstract: We investigated the association between human polymorphonuclear leukocytes (PMNs) and non‐opsonized Tannerella forsythia ATCC 43037 displaying a serum‐resistant surface layer (S‐layer). When PMNs were mixed with T. forsythia in suspension, the cells phagocytosed T. forsythia cells. Nitro blue tetrazolium (NBT) reduction, indicative of O 2 − production, was observed by light microscopy; cerium (Ce) perhydroxide deposition, indicative of H2 O2 production, was observed by electron microscopy. We examined the relationship between high‐molecular‐weight proteins of the S‐layer and Ce reaction (for T. forsythia phagocytosis) using electron microscopic immunolabeling. Immunogold particles were localized within the PMNs and on cell surfaces, labelling at the same Ce‐reacted sites where the S‐layer was present. We then used energy dispersive spectroscopy (EDS)‐scanning transmission electron microscope (STEM) to perform Ce and nitrogen (N) (for S‐layer immunocytochemistry) elemental analysis on the phagocytosed cells. That is, the elemental mapping and analysis of N by EDS appeared to reflect the presence of the same moieties detected by the 3, 3′‐diaminobenzidine‐tetrahydrochloride (DAB) reaction with horseradish peroxidase (HRP)‐conjugated secondary antibodies, instead of immunogold labeling. We focused on the use of EDS‐STEM to visualize the presence of N resulting from the DAB reaction. In a parallel set of experiments, we used EDS‐STEM to perform Ce and gold (Au; from immunogold labeling of the S‐layer) elemental analysis on the same phagocytosing cells. Abstract : We investigated the association between leukocytes and T. forsythia ( T.f. ) by EDS‐STEM. We detected Ce, H2 O2 production, and nitrogen (S‐layer from T. f, DAB with HRP instead of immunogold labeling) elements on the same sites of leukocyte cytoplasm.